Arc related dioritic–granodioritic magmatism from southeastern Peninsular Malaysia and its tectonic implication - Hazad, Fatin Izzani; Ghani, Azman Abd; Lo, Ching Hua (Elsevier, 2019)
In Peninsular Malaysia, Late Cretaceous (95-76 Ma) plutons are found within the Eastern Belt. Their compositions are diverse, ranging from biotite granite, hornblende granodiorite, diorite, and gabbro. The Aur Pluton is the easternmost body and is exposed in the Johore Archipelago, southeast of Peninsular Malaysia. The rock types vary from diorite, quartz monzodiorite and granodiorite. Ar-Ar stepheating age of the diorite and zircon U/Pb age of the granodiorite yielded ages of 77.9 ± 2 Ma and 79 ± 0.7 Ma, respectively. The overall major and trace element trends are consistent with two magmatic pulses, i.e., diorite-quartz monzodiorite and granodiorite. The diorite-quartz monzodiorites are characterized by high Fe2O3 (6.7–8.3 wt.%), CaO (5.5–7.6 wt.%), MgO (2.9–4.1 wt.%) and high but variable Sr concentrations (570–1300 ppm). The granodiorites have significantly higher total alkali content (8.49–8.91%), with high K2O concentrations (3.8–4.6%) and low Fe2O3 (4.7–6.5%), CaO (2.7–3.9%) and MgO (1.4–2.0%) concentrations. Low Nb/U and distinct Pb anomalies suggest that both rock types are likely derived from the crust. Furthermore, elevated LREE and trace element contents for the granodiorites, e.g., FTh (10–20 ppm), Pb (10–30 ppm), and U (2–5 ppm), also indicate that upper crustal components are involved in the magma generation. The dioritic rocks are chemically classified as calc-alkaline volcanic arc (VAG) rocks, but they also have field relationships and mineralogies typically associated with an active continental margin (ACM).